Towards dynamic multiscale feedback during the injection moulding cycle of plastics - Massano, Anabela P.; Vargas, Patricio; Carreira, Pedro; Matias, Joao; Malfois, Marc; Novo, Paulo J.; Martinho, Pedro; Pontes, Antonio; Mitchell, Geoffrey R. (Frontiers in Materials, 2024)
Injection moulding is a very popular technology for shaping plastics. Its history stretches back to the nineteenth century, and, as a consequence, it has developed outside the framework of digitisation. In order to fully implement the concepts of Industry 4.0, we need to update these legacy technologies so that they can fully benefit from the developments inherent in the “Internet of Things” and allow the process of injection moulding to take full advantage of digital optimisation so that it can fit effectively in the digital factory. In this work, we explore the quantitative use of X-ray scattering as a technology that can provide dynamic and multiscale feedback during the injection moulding cycle to be able to exploit digital twin technology as a means to optimise the operational parameters involved in injection moulding and to enable digital design of moulds in the fullest sense. This manuscript provides a way to mark future work and draw these possibilities to a wider audience.